Better long-term speech outcomes in stroke survivors who received early clinical speech and language therapy: What's driving recovery?. Issue 9 (21st October 2022) - Roberts, Sophie; Bruce, Rachel M.; Lim, Louise; Woodgate, Hayley; Ledingham, Kate; Anderson, Storm; Lorca-Puls, Diego L.; Gajardo-Vidal, Andrea; Leff, Alexander P.; Hope, Thomas M. H.; Green, David W.; Crinion, Jennifer T.; et al.
ABSTRACT: Establishing whether speech and language therapy after stroke has beneficial effects on speaking ability is challenging because of the need to control for multiple non-therapy factors known to influence recovery. We investigated how speaking ability at three time points post-stroke differed in patients who received varying amounts of clinical therapy in the first month post-stroke. In contrast to prior studies, we factored out variance from: initial severity of speaking impairment, amount of later therapy, and left and right hemisphere lesion size and site. We found that speaking ability at one month post-stroke was significantly better in patients who received early therapy ( n  = 79), versus those who did not ( n  = 64), and the number of hours of early therapy was positively related to recovery at one year post-stroke. We offer two non-mutually exclusive interpretations of these data: (1) patients may benefit from the early provision of self-management strategies; (2) therapy is more likely to be provided to patients who have a better chance of recovery (e.g., poor physical and/or mental health may impact suitability for therapy and chance of recovery). Both interpretations have implications for future studies aiming to predict individual patients' speech outcomes after stroke, and their response to therapy.